Insidious Harm of Medication Diluents as a Contributor to Cumulative Volume and Hyperchloremia: A Prospective, Open-Label, Sequential Period Pilot Study*. Issue 8 (August 2018) - Magee, Carolyn A.; Bastin, Melissa L. Thompson; Laine, Melanie E.; Bissell, Brittany D.; Howington, Gavin T.; Moran, Peter R.; McCleary, Emily J.; Owen, Gary D.; Kane, Lauren E.; Higdon, Emily A.; Pierce, Cathy A.; Morris, Peter E.; et al.
Abstract : Objectives: Although the potential dangers of hyperchloremia from resuscitation fluids continue to emerge, no study to date has considered the contribution of medication diluents to cumulative volume and hyperchloremia. This study compares saline versus dextrose 5% in water as the primary medication diluent and the occurrence of hyperchloremia in critically ill patients. Design: Prospective, open-label, sequential period pilot study. Setting: Medical ICU of a large academic medical center. Patients: Adult patients admitted to the medical ICU were eligible for inclusion. Patients who were admitted for less than 48 hours, less than 18 years old, pregnant, incarcerated, or who had brain injury were excluded. Interventions: Saline as the primary medication diluent for 2 months followed by dextrose 5% in water as the primary medication diluent for 2 months. Measurements and Main Results: A total of 426 patients were included, 216 in the saline group and 210 in the dextrose 5% in water group. Medication diluents accounted for 63% of the total IV volume over the observation period. In the saline group, 17.9% developed hyperchloremia compared with 10.5% in the dextrose 5% in water group ( p = 0.037), which was statistically significant in multivariable analysis (odds ratio, 0.50; 95% CI, 0.26–0.94; p = 0.031). In the saline group, 34.2% developed acute kidney injury versus 24.5% in the dextrose 5% in water group ( p = 0.035); however, this was not statistically significant when adjusting for baseline covariates. No other significant differences in dysnatremias, insulin requirements, glucose control, ICU length of stay, or ICU mortality were observed. Conclusions: This study identified that medication diluents contribute substantially to the total IV volume received by critically ill patients. Saline as the primary medication diluent compared with dextrose 5% in water is associated with hyperchloremia, a possible risk factor for acute kidney injury. Abstract : Supplemental Digital Content is available in the text.